Perspectiva de rede de atenção à saúde de crianças e adolescentes vivendo com HIV - Kinalski, Daniela Dal Forno (2016)
Children living with Human Immunodeficiency Virus (HIV) or Acquired Immune Deficiency Syndrome (AIDS) require health-monitoring demands beyond the usual, due to the specifics of their HIV status. Among the demands, there is the ongoing control of health and dependence on drug technology. However, the fragility to access services of Primary Health Care (PHC) results in an engagement with specialized services. It is recommended that specialized services benefit themselves from the APS services, towards the quality of health care, preferably coordinated by APS. In this sense is that the realization of a Network Health Care (NHC) want integration between services, consistent with the public policy of national health. Thus, it is necessary to structure the municipal policy to implement a transfer system, defining the responsibility activities of each service and continuing education of professionals who need to know the children and adolescents living with HIV in their area, and develop actions of commitment and strengthen bonds. In this sense, this research has the aim of discussing with the professionals the NHC of children and adolescents living with HIV, perspectives care line and flow in the city of Santa Maria, Rio Grande do Sul, Brazil. Methodology: qualitative approach conducted through the technique of focus groups with 23 health professionals, PHC and specialized service, totaling four sessions. The study setting was the PHC services of Santa Maria, the University Hospital of Santa Maria and Casa Treze de Maio. Content Analysis and respected the ethical aspects of research involving human beings, according to the Resolution 466/12 of the National Health Council were developed. Results: The health care of children and adolescents living with HIV in Santa Maria is performed in specialized services . This is due to conceptual, structural and social aspects. To this end, in an attempt to decentralize this health care model in specialties, it was discussed and rearranged this attention to health through the construction of a line of care for this population. The conceptions of each point of attention have been defined, the articulations and the necessary operationalizations for better integration between the health care points. It is noteworthy that this dissertation was a product: the flow of health care for children and adolescents living with HIV in Santa Maria. Final thoughts: the discussions provided the reorganization of a care model that was fragmented, focusing on the clinical management of the disease to a model of attention to health shared between points based on the principles of RAS.